A construção do diálogo socrático como exercício da atividade filosófica em sala de aula a partir de uma leitura kierkegaardiana - Xavier, Eldon Cavalcante (2023)
How important is Socrates to the present day? What can the method developedby him contribute to the teaching and learning of philosophy? This work consists of analyzing the use of the Socratic method in philosophy classes with teeenagers in high school. Thinking of a way of working the philosophy discipline, so that students can develop aspects and skills, such as: the discovery of themselves and the world around them, as well as na expansion of their critical sense and capacity for reflection and interpretation through dialogue and contact with the method used by Socrates. We will talk about all the points that make up the Socratic method. Starting with not knowing, going through irony and maieutics, always demonstrating how it was applied and the students’ reaction to the contact with this form of philosophical approach. In this way, we will demonstrate though classroom practice, how the construction of dialogue is done, and how it provides a higher level of learning and interaction on the part of students.